2010
DOI: 10.1186/1471-2105-11-s6-s8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic subnetwork markers for cancer in human protein-protein interaction network

Abstract: BackgroundFinding reliable gene markers for accurate disease classification is very challenging due to a number of reasons, including the small sample size of typical clinical data, high noise in gene expression measurements, and the heterogeneity across patients. In fact, gene markers identified in independent studies often do not coincide with each other, suggesting that many of the predicted markers may have no biological significance and may be simply artifacts of the analyzed dataset. To find more reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 30 publications
(49 reference statements)
0
44
0
Order By: Relevance
“…Recently several studies defined cancer phenotypeassociated PPI subnetworks by their correlative changes in gene expression to phenotype variations (Chuang et al, 2007;Dao et al, 2010;Su et al, 2010). The PPI subnetworks provided insights into pathways involved in tumor progression and were more reproducible markers of cancer prognosis than individual genes selected without network information (Chuang et al, 2007;Dao et al, 2010;Su et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently several studies defined cancer phenotypeassociated PPI subnetworks by their correlative changes in gene expression to phenotype variations (Chuang et al, 2007;Dao et al, 2010;Su et al, 2010). The PPI subnetworks provided insights into pathways involved in tumor progression and were more reproducible markers of cancer prognosis than individual genes selected without network information (Chuang et al, 2007;Dao et al, 2010;Su et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating PPI networks with expression data, for example, led to the identification of cancer susceptibility genes and oncogenes in breast carcinomas [122], B-cell acute myeloid lymphomas [123,124]; the identification of markers for metastasis in breast [125,126], colorectal [127,128] and gastric [129] cancer; the prediction of disease outcome [130] and response to chemotherapy [131,132] and the determination of therapy-resistance genes [133,134]. By combining protein-protein and protein-DNA interaction studies Kim et al identified a Myc-centered regulatory network in embryonic stem cells, and showed that the Myc module is active in various cancers and predicts cancer outcome [135].…”
Section: Disease Disease Gene or Pathway Referencementioning
confidence: 99%
“…In order to evaluate the efficacy of the predicted subnetwork markers in cancer prognosis, we performed five-fold cross-validation experiments based on a similar set-up that has been commonly used in previous studies [3][4][5][6][7].…”
Section: Evaluating the Reproducibility Of The Predicted Subnetwork Mmentioning
confidence: 99%
“…Examples of such modular markers include the pathway markers [1][2][3][4][5] and the subnetwork markers [6,7]. A pathway marker consists of multiple genes that belong to the same functional pathway.…”
Section: Introductionmentioning
confidence: 99%